2009
DOI: 10.1038/onc.2009.367
|View full text |Cite
|
Sign up to set email alerts
|

LIM-kinase 2, a regulator of actin dynamics, is involved in mitotic spindle integrity and sensitivity to microtubule-destabilizing drugs

Abstract: LIM-kinase 2 (LIMK2) belongs to the LIMK family of proteins, which comprises LIMK1 and LIMK2. Both proteins regulate actin polymerization through phosphorylation and inactivation of the actin depolymerizing factor cofilin. In this study, we show that the level of LIMK2 protein is increased in neuroblastoma, BE(2)-C cells, selected for resistance to microtubule-destabilizing agents, vincristine and colchicine. However, the level of phosphorylated LIMK1 and LIMK2 was similar in the resistant and parental BE(2)-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 34 publications
4
41
1
1
Order By: Relevance
“…An inference from this study is that because LIMK2 levels are decreased in a sizeable proportion of CRC patients, these cancers might be more effectively treated with some chemotherapeutics because knocking down and/or inhibiting LIMK2 sensitises cancer cells to DNA damaging agents,17 Aurora A inhibitors,54 Ras inhibition55 and microtubule-destabilising drugs such as vincristine and vinblastine 56. Therefore, knowledge of LIMK2 expression levels in CRC may have utility in patient stratification for the development of personalised therapies.…”
Section: Discussionmentioning
confidence: 91%
“…An inference from this study is that because LIMK2 levels are decreased in a sizeable proportion of CRC patients, these cancers might be more effectively treated with some chemotherapeutics because knocking down and/or inhibiting LIMK2 sensitises cancer cells to DNA damaging agents,17 Aurora A inhibitors,54 Ras inhibition55 and microtubule-destabilising drugs such as vincristine and vinblastine 56. Therefore, knowledge of LIMK2 expression levels in CRC may have utility in patient stratification for the development of personalised therapies.…”
Section: Discussionmentioning
confidence: 91%
“…Additional evidence comes from the observations that LIMK1 is localized to the centrosomes and LIMK2 to the mitotic spindles (Sumi et al, 2006). Knocking down LIMK2 also increases the number of abnormal spindles in cells treated with microtubule-destabilizing drugs (Po'uha et al, 2010). Interestingly, it has also been reported that ROCK phosphorylates LIMK2 downstream of RhoA activation (Sumi et al, 2001), but not LIMK1, which is phosphorylated by the PAK kinases (Edwards et al, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, knockdown of LIMK2 in cell lines results in significantly reduced neurite bearing cell count, neurite length, and cone extension growth rate 29. Furthermore, LIMK2 expression has been implicated in sensitivity to the microtubule binding agents vincristine and vinblastine in a neuroblastoma cell line 30. With respect to other genes at this locus, PIK3IP is a negative regulator of PI3K and PLA2G3 is involved in oxidative stress and is associated with Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%